Math handbook : quick review course 3 (New Yorkn : Mc Graw Hill, 2004)
Quick Review Math Handbook: Hot Words, Hot Topics (available in English and Spanish) provides students and parents with a comprehensive reference of important mathematical terms and concepts to help them build their mathematics literacy. This handbook also includes short-instruction and practice of key standards for Middle School and High School success.
Includes index.
Keywords: Mathematics -- Education (Middle school) -- Problems, exercises, etc; Mathematics -- Study and teaching -- Education (Middle school).